Biochemical and demographical study of lipid profile in sera of patientswith gallstone - Al-Saadi, Narjis; Al-Ardhi, Sabah (Iraqi Journal of Science, 2024)
Thirty patients with gallstone [aged 25-55 years]and thirty age-and sex-matchedhealthy subjects as control group were involved. Those patients were intended toundergo surgical removal of gallbladder in the surgical ward- Al Sadder TeachingHospital and AL-Hakeem Hospital in Najaf city during the period from July/2009 toDecember /2009. The proportion of female was [86%] compared to the male t[14%]. The ratio of female: male was 5:1. Blood samples were obtained from allpatients prior to surgery. Serum was obtained by usual methods and analyzed forlipid profile test [total cholesterol [TC], triglyceride [TG], high density lipoprotein-cholesterol [HDL-C], low density lipoprotein cholesterol [LDL-C] and very lowdensity lipoprotein cholesterol [VLDL-C]}. The results showed that there were nosignificant differences between gallstone patients and control regarding HDL-C[p>0.05] but there was highly significant [p<0.05] difference in the concentrationsof total cholesterol [TC], triglyceride [TG] and VLDL-C comparing with the controlgroup. The study also showed that the sex has a significant effect [p<0.05] on thelevels of TC, LDL-C, and VLDL-C in sera of patients with gallstone whereas, nonsignificant sex variation had found with respect to HDL-C level. On the other hand,it was also found that there was a significant p<0.05 ] age variations with respect toserum levels of TC, TG and VLDL-C with effect with respect to both HDL-C andLDL-C levels in sera of patient with gallstone. Additionally, all items of lipid panelfound to be significantly [p<0.05] varied with respect to the BMI. Similarly,smoking was found to be important cause and revealed a significant [p<0.05]difference regarding all parameters- but not LDL-C of lipid components.The objective of this study was to estimate the serum lipid profile, in sera of patientswith gallstone and investigate their relationship with demographic factors.